Agglomeration Processes in Modern Urban Planning (On the Example of Bukhara Agglomeration) - Muhammadovich, Mavlonov Ahmadjon; Zakirovna, Hayotova Nafisa (European Journal of Life Safety and Stability (2660-9630), 2021)
This article focuses on the process of agglomeration, one of the manifestations of modern urbanization—the definition of agglomeration, the process of formation, agglomerations in Uzbekistan. The current state of formation and development of the Bukhara agglomeration is also covered.